The fundamentals of money and financial systems - Naghshpour, Shahdad. (2013 digital library., 2013)
It is impossible to comprehend what policies the government should undertake to face the economic reality of the country. Every day the public is exposed to a barrage of recommendations and mandates from the left and the right concerning what would be the appropriate course of action or lack thereof in order to nullify economic ills or to bring prosperity to the country. A fundamentally basic requirement to being able to comprehend these claims is the knowledge of money. It is important to understand the meaning of money and be able to differentiate between basic concepts such as consumption, savings, capital, and investment. Would it make any difference, to the overall function of the economy, earnings, employment, etc. if a given sum of money is spent by an individual, a small business, a corporation, or the government? Is it good for the country if people spend money or is it better if they save it? Would it make a difference if spending originates from printing money or citizens' savings? The answer to these and many other economic questions are at the heart of the fiscal and monetary policy that every government grapples with every day. It is essential to know the role of money and how it fits into the answers to these and other policy questions. This book provides the necessary foundations for understanding money and many of its functions, roles, and uses in economic theories that are essential to comprehend economic theories needed for formulation of fiscal and monetary policies. This book is not a textbook to be used in a course in money and banking in a typical economic program. It is written for executives and decision makers who need to comprehend the meanings of different policies and how they affect their decisions in their business or private life but cannot even begin the process because they are unaware of the basic block of fiscal and monetary policy, namely money. Many people use the words like capital, savings, and investments interchangeably or as close substitutes. However, each one has a specific meaning and purpose in economics. After reading this book you will be ready to understand the fiscal and monetary policies, tools, and effectiveness.